Innovation And Promotion Of Business Units And Educational Institutions - Mupti Al Umam; Dumyati; Rahmat Fajar Al-Qusyairi JNZ; Holilur Rahman (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2026)
Innovation and promotion are two important aspects in the development of business units and educational institutions. Innovation can help improve the quality of the product or service offered, while promotion can help introduce the product or service to the wider community. Innovation in business units and educational institutions involves the development of new ideas, methods, or approaches that can improve the quality, efficiency, and relevance of the products or services offered. Innovation can include the development of new technologies, changes in the teaching process, the development of more relevant curricula, or the use of innovative learning methods. The objectives of this research are 1) to find out the meaning of innovation of business units and educational institutions, 2) to find out the meaning of promotion of business units and educational institutions. The type of research used in this study is library research with a qualitative research method that is descriptive in an effort to uncover a problem or event as it is. Product innovation is an effort carried out by a company to create new products that aim to adapt to consumer tastes and can increase sales. Meanwhile, educational innovation is a new and qualitative change that is different from the previous one, and is deliberately sought to improve the ability to achieve certain goals in education.